Problem posing in Primary School: an exploratory study on multiplicative arithmetical problems (Edma 0-6: Educación Matemática en la Infancia, 2021)
The main objective of this work consists in carrying out an exploratory study on the 10-11 year-old elementary school pupils’ knowledge of multiplicative structure problems. The enquiry on the students’ knowledge is done through multi-step arithmetical problem posing tasks. The experimental design comprises two stages: the first one, a brief training in problem posing; the second one, the collection of data, in which students had to pose problems based on a given picture. The analysis of the problems posed reveals a marked tendency of the students to formulate problems pertaining to the isomorphism of measures category, even if the contexts evoke other semantic categories of multiplicative problems.
Keywords: Elementary School; Arithmetical word problems; Problem solving; Problem posing; Case study; Multiplicative problems